MITOXANTRONE INTERACTION WITH POLY(G) - Karapetyan, A.T.; Babayan, Yu.S.; Torosyan, M.A.; Shahinyan, M.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
In the present work the thermodynamic studies of mitoxantrone complexformation with four-stranded poly(G) have been carried out. The binding thermodynamic parameters, the binding constant K and the number of nucleotides corresponding to one binding site n, were determined. It was shown that mitoxantrone is bound stronger with four-stranded poly(G), then it is bound with double-stranded helix. It was also shown that due to difficulties of the intercalation of mitoxantrone molecules into four-stranded structure is bound mainly by external binding mode with [poly(G)]4 and at the interaction saturation mitoxantrone bound to much more guanines (n10) per one molecule.